Quality assessment: importance of external evaluation and monitoring - Tarí Guilló, Juan José; de Juana Espinosa, Susana Amalia; Mora Pascual, Jerónimo Manuel (Avances en Supervisión Educativa, 2007)
The aim of this paper is to illustrate the steps to develop a quality assessment and analyse the importance of external assessment and follow-up in a university. The paper highlighted that the external examiner must suggest recommendations and that a follow-up is a need to the success of this process.